Why has income inequality in Germany increased from 2002 to 2011? A behavioral microsimulation decomposition - Robin Jessen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
I propose a method to decompose changes in income inequality into the contributions of policy changes, wage rate changes, and population changes while considering labor supply reactions. Using data from the Socio-Economic Panel (SOEP), I apply this method to decompose the increase in income inequality in Germany from 2002 to 2011, a period that saw tax reductions and a controversial overhaul of the transfer system. The simulations show that tax and transfer reforms have had an inequality reducing effect as measured by the Mean Log Deviation and the Gini coefficient. For the Gini, these effects are offset by labor supply reactions. In contrast, policy changes explain part of the increase in the ratio between the 90th and the 50th income percentile. Changes in wage rates have led to a decrease in income inequality. Thus, the increase in inequality was mainly due to changes in the population.
Keywords: D31; H23; I38; J31; 330; Inequality; Decomposition; Labor Supply; Microsimulation; Policy Reform